Divergent responses of plant and soil microbial community to short-term nutrient addition in alpine grassland on the Qinghai-Tibetan Plateau - Du, Juan; Tan, Tianyuan; Jiang, Shengjing (Frontiers in Ecology and Evolution, 2022)
Nitrogen (N) and phosphorus (P) are the main restrictive elements in terrestrial ecosystems, which have an important role in determining the community composition of plants and soil microorganisms. However, there is still a lack of understanding about whether plant and soil microbes respond synchronously to external N and P addition deposition, particularly on a short time scale (< 1yr). Here, we conducted a short-term experiment (3 months) involving control, N addition, P addition, and N+P addition in an alpine grassland on the Qinghai-Tibetan Plateau. Responses of plant and soil microbial (bacterial and fungal) communities were analyzed using the quadrat method and high-throughput sequencing, respectively. N addition significantly increased aboveground biomass and changed the plant community composition, but had no significant effect on soil microbes. Thus, microbial and plant processes were asynchronous following the resource availability in this alpine meadow. According to our research, the plant community may react to short-term nutrient deposition more quickly than the soil microbial community.